Preparation and Properties of Natural Leather-Tungsten Fast Neutron Moderating Materials - Jinchao ZENG; Jibo ZHOU; Hao LI; Xuepin LIAO; Bi SHI (Pige Kexue Yu Gongcheng)
A composite neutron moderating material, designated NL/Wn@AR, was fabricated using natural leather (NL) as the base material and carboxylated tungsten nanoparticles (W@AR) as the functional component. The composite material was prepared with varying tungsten molar concentrations of 0.76, 2.85, 5.12, and 6.98 mmol/cm³, respectively. The energy attenuation behavior of NL/Wn@AR for 4.4 MeV neutrons was simulated using the Monte Carlo N-Particle (MCNP) code. Simulation results indicated that the moderating ability of NL/Wn@AR was enhanced with the increase of thickness. At a given thickness, the moderated thermal neutron flux of NL/W@AR with 5.12 mmol/cm³ tungsten concentration approximated that of polyethylene, while NL/W@AR with 6.98 mmol/cm³ tungsten concentration surpassed it. Experimental validation of the material’s moderating capacity was conducted using an Am-Be neutron source. The experimental results aligned with MCNP simulations, confirming that after moderation, NL/W@AR with 5.12 mmol/cm³ tungsten concentration exhibited comparable performance to polyethylene, while NL/W@AR with 6.98 mmol/cm³ tungsten concentration demonstrated superior effectiveness. Notably, NL/Wn@AR possesses enhanced physical and mechanical properties compared to polyethylene while maintaining excellent neutron moderating ability, highlighting its potential for diverse applications.